2005
DOI: 10.1080/03079450500112195
|View full text |Cite
|
Sign up to set email alerts
|

Intercurrent coccidiosis and necrotic enteritis of chickens: rational, integrated disease management by maintenance of gut integrity

Abstract: Coccidiosis and necrotic enteritis (NE) are globally common, sometimes intercurrent, diseases of poultry. The risk of NE, due to the Gram-positive bacterium Clostridium perfringens, has increased in recent years because of the voluntary or legally required withdrawal of the use of certain in-feed antibiotic growth promoters with anticlostridial activity. In-feed ionophorous anticoccidial drugs incidentally also possess anticlostridial activity. Such ionophores, although not banned, are usually precluded when l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
319
0
19

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 422 publications
(355 citation statements)
references
References 228 publications
10
319
0
19
Order By: Relevance
“…a varying mortality rate occurs (Williams, 1996). It has been shown to increase the risk of NE occurrence (Al-Sheikhly & Al-Saieg, 1980) by damage of epithelia (Williams, 2005), protein leakage and increase of mucus secretion allowing C. perfringens to replicate and produce toxins (Van Immerseel et al, 2004, 2009Collier et al, 2008;Cooper & Songer, 2010). NE was effectively prevented by mixing antimicrobial growth promoters in the broiler feed (Elwinger et al, 1998;Lanckriet et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…a varying mortality rate occurs (Williams, 1996). It has been shown to increase the risk of NE occurrence (Al-Sheikhly & Al-Saieg, 1980) by damage of epithelia (Williams, 2005), protein leakage and increase of mucus secretion allowing C. perfringens to replicate and produce toxins (Van Immerseel et al, 2004, 2009Collier et al, 2008;Cooper & Songer, 2010). NE was effectively prevented by mixing antimicrobial growth promoters in the broiler feed (Elwinger et al, 1998;Lanckriet et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the emergence of bacterial resistance, the use of antibiotics is and will be further diminished. Various methods for NE prophylaxis have been investigated; for example, treatment with ionophorous anticoccidial drugs (Williams, 2005) or a so far experimental approach of vaccination with a C. perfringens toxoid vaccine (Mot et al, 2013). The effect of anticoccidials in a subclinical NE model was tested by Lanckriet et al (2010) and narasin, maduramicine and salinomycine showed a certain efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Necrotic enteritis (NE) is an acute or chronic enterotoxaemia caused by Clostridium perfringens (van der Sluis 2003;Williams 2005). C. perfringens is a Gram-positive, obligate anaerobic, spore-forming bacterium readily found in soil, dust, used poultry litter and as a normal inhabitant of the gut microflora of healthy birds (Dahiya et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Since the ban of using antibiotics as growth-promoters in the animal feed, the concept of digestive flora and the management of bacterial balance of digestive tract have become more important. Digestive disorders have increased in parallel to this withdrawal (Van Immersel et al, 2004) and are often sources of under performances due to healthy problem as necrotic enteritis or coccidiosis (Williams, 2005).…”
Section: Introductionmentioning
confidence: 99%